The main stages of management accounting - Giyosov Ilhom Karimovich (International Consortium of Education and Culture Research Studies, 2019)
This paper makes analyses of the research on management accounting. On this way, the main stages of management accounting are mentioned on the analyses. It concludes major points of the research on accounting and management